Phenolic Profile, Antioxidant, Anti-Cholinesterase, and Anti-Alpha-Amylase Activities of Algerian Ruta graveolens - Amira Randa Rimas Meziane; Hind Fenghour; Hanane Seghier; Hayette Bouabida; Ghania Dilekh; Chawki Bensouci; Mustafa Abdullah Yilmaz; Oguz Cakir; Abbas Tarhan (Bogor Agricultural University, Indonesia, 2026)
Ruta graveolens, belonging to the Rutaceae family, is a medicinal and aromatic plant. It is widely used in traditional Algerian medicine. As part of our contribution to promoting this medicinal plant, we conducted an in-depth study to analyze its phenolic content and evaluate its antioxidant, anti-alzheimer and antidiabetic properties. Our methodical approach consisted of studying the hydroethanolic extract of Ruta graveolens leaves, a plant with well-documented pharmacological properties. The extraction was carried out by maceration under agitation, using a solvent, namely 70% ethanol. The LC-ESI-MS/MS analysis was utilized to identify 14 compounds, revealing the richness of this species in polyphenols and flavonoids, particularly in hesperidin and rutin. In addition, Antioxidant activity is assessed using various recognized scientific tests, the hydroethanolic extract is distinguished by its remarkable ability to trap the DPPH radical, with an IC50 of 43.20±0.96 mg/mL. It also exhibits strong antioxidant activity, as evidenced by IC50 values of 38.01±2.96 mg/mL obtained by the ABTS test and 102.96±3.26; 312.29±6.8; 192.07±6.75 mg/mL by the FRAP, β-carotene and SNP tests respectively. The cholinesterase inhibition was also investigated in this work, specifically against cholinesterase enzymes: acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Analysis of the extract revealed significant antidiabetic activity, by inhibiting α-amylase enzyme and for the first time, the Algerian Ruta graveolens was reported to inhibit cholinergic and α-amylase enzymes. At the end of this study, it appears that the plant studied has notable biological activities and could be an excellent natural biological product for use in the pharmaceutical field.